INFORMATION SUPPORT IN THE FIELD OF CORPORATE SOCIAL RESPONSIBILITY: PROBLEMS AND DEVELOPMENT - A. A. Yarysh (Финансы: теория и практика, 2017)
The paper deals with the disclosure of information on social responsibility and social obligations in corporate reporting. The trends in the circulation of non-financial social responsibility reporting as well as the problems of its application in Russia are analyzed. The constraints and shortcomings of using non-financial reporting have been revealed in the context of providing concerned users with full information about the social responsibility. It is established that the financial statements of a company have a significant potential for disclosing such information and can serve as an addition as well as an alternative to the non-financial reporting in this area. The problems are identified and directions for the application of both types of reporting are proposed in terms of providing reliable and timely information about the social responsibility of an enterprise.